CELL-AUTONOMOUS HEDGEHOG SIGNALING CONTROLS TH17 DIFFERENTIATION TO DRIVE INTESTINAL INFLAMMATION AND IS A DRUGGABLE TARGET FOR THE TREATMENT OF INFLAMMATORY BOWEL DISEASE. (22nd January 2022) - Hanna, Joachim; Beke, Flavio; O'Brien, Louise; Kapeni, Chrysa; Chen, Hung-Chang; Carbonaro, Valentina; Kim, Alexander; Adolph, Timon E; Skjoedt, Mikkel-Ole; Karsten, Skjoedt; de la Roche, Marc; de la Roche, Maike
Abstract: BACKGROUND: T helper 17 (Th17) cells play a key role in barrier protection in the gastrointestinal tract but are also key pathological drivers of Inflammatory Bowel Disease (IBD). Although a number of key transcription factors governing Th17 differentiation have been identified, the intracellular signaling pathways regulating Th17 differentiation are poorly understood. Given the highly druggable nature of many intracellular signaling pathways, understanding the signaling pathways involved in Th17 differentiation holds great promise to identify novel drug targets for the treatment of IBD. Hedgehog (Hh) signaling controls cell-fate choices in numerous tissue compartments and is targetable by highly selective, clinically-approved small molecule inhibitors. However the role of Hh signaling in Th17 differentiation and effector function is unstudied. METHODS: We generated two conditional knockout mouse models targeting Hh signaling components Smo and Ihh to study Th17 differentiation and effector function in vitro and in vivo in murine T cell adoptive transfer colitis. We supplement this with the use of two small-molecule Smo antagonists for both in vitro and in vivo studies of Th17 function. To underscore the translational relevance of our findings, we have conducted bioinformatic analyses of published gene expression datasets of human rectal biopsies from two large independent cohorts of Ulcerative Colitis patients and healthy controls as well as from sorted human effector T cells from blood and lamina propria of healthy individuals. RESULTS: We find that intracellular Hh signaling, independently of extracellular Hh ligands, selectively drives differentiation and effector function of Th17 cells but not of other T helper cell lineages. Using two models of intestinal inflammation, we demonstrate that inhibition of the Hh pathway with either the clinically-approved small molecule inhibitor vismodegib or genetic ablation of Ihh in CD4 + T cells profoundly diminishes disease severity and Th17-induced pathology in the intestine. Our bioinformatic analyses show that Hh component expression levels are upregulated in human ulcerative colitis patient samples and are closely correlated with expression of Th17 markers/cytokines. Mechanistically we show that the T-cell-intrinsic Indian Hedgehog (Ihh) ligand signals via the signal transducer Smoothened to activate both canonical and non-canonical Hh pathways, through the Gli3 transcription factor and AMPK phosphorylation, respectively. CONCLUSIONS: We uncover Hh signaling as a novel pathway controlling Th17 differentiation and pathogenicity in IBD with Gli3 acting as a newly-identified crucial regulatory transcription factor. Our work paves the way for the use of Hh inhibitors for the treatment of IBD.